Medical Record Keeping in the Summer Camp Setting - Kaufman, Laura; Holland, Jaycelyn; Weinberg, Stuart; Rosenbloom, S. Trent (Applied Clinical Informatics, 2016)
Background Approximately one fifth of school-aged children spend a significant portion of their year at residential summer camp, and a growing number have chronic medical conditions. Camp health records are essential for safe, efficient care and for transitions between camp and home providers, yet little research exists regarding these systems.Objective To survey residential summer camps for children to determine how camps create, store, and use camper health records. To raise awareness in the informatics community of the issues experienced by health providers working in a special pediatric care setting.Methods We designed a web-based electronic survey concerning medical recordkeeping and healthcare practices at summer camps. 953 camps accredited by the American Camp Association received the survey. Responses were consolidated and evaluated for trends and conclusions.Results Of 953 camps contacted, 298 (31%) responded to the survey. Among respondents, 49.3% stated that there was no computer available at the health center, and 14.8% of camps stated that there was not any computer available to health staff at all. 41.1% of camps stated that internet access was not available. The most common complaints concerning recordkeeping practices were time burden, adequate completion, and consistency.Conclusions Summer camps in the United States make efforts to appropriately document healthcare given to campers, but inconsistency and inefficiency may be barriers to staff productivity, staff satisfaction, and quality of care. Survey responses suggest that the current methods used by camps to document healthcare cause limitations in consistency, efficiency, and communications between providers, camp staff, and parents. As of 2012, survey respondents articulated need for a standard software to document summer camp healthcare practices that accounts for camp-specific needs. Improvement may be achieved if documentation software offers the networking capability, simplicity, pediatrics-specific features, and avoidance of technical jargon.Citation: Kaufman L, Holland J, Weinberg S, Rosenbloom ST. Medical record keeping in the summer camp setting.
Keywords: Documentation; summer camp; infirmary; informatics; medical record